The social consequences of transport decision-making : clarifying concepts, synthesising knowledge and assessing implications - Jones, P; Lucas, K (Elsevier, 2012)
In this paper, we seek to highlight the importance of understanding the social impacts and consequences, as well as the distributional effects, of transport decision-making. Based on an extensive review of the contemporary literature, we aim to clarify key concepts and definitions around the notion of social impacts and to give them an identity distinct from economic and environmental impacts and from existing notions of ‘distributional issues’. We primarily focus on five short-term or ‘immediate’ categories of social impact, namely accessibility, movement and activities, health-related, financial related and community-related impacts. We then consider the spatial, temporal and socio-demographic distributional effects of transport at every level of planning, policy and systems delivery. We also briefly discuss some of the longer-term social consequences of these social impacts in terms of health, individual and community wellbeing and social equity and justice. The paper is designed as an introduction to a wider discussion of these themes in this Special Issue Social Impacts and Equity Issues in Transport. Our overall aim for the paper is to demonstrate that, by overlooking the social impacts and social equity implications of transport decision-making at every level of the decision-making process, we are fundamentally undermining quality of life and social well-being in our towns, cities and rural settlements. Conversely, we believe that integration and consideration of the social impacts of transport planning and delivery can significantly increase the quality, effectiveness and efficiency of a number of other important areas of economic and social policy, including employment, health, education and economic development.